The Necessity to Expand the Surface of Protected Areas in Romania: Array - Dobrescu, Codruța Mihaela; Turtureanu, Anca; Dorobăț, Leonard Magdalin (Journal of Danubian Studies and Research, 2020)
The protected natural areas are those areas where we find the most representative and valuable elements of the natural heritage (heritage). On the Globe there are a multitude of categories, of ranks of protected areas, from nature monuments, to National Parks and Biosphere Reservations, from areas under one hectare to hundreds of thousands of square kilometers. The EU has in the field of nature protection the European Ecological Network Natura 2000; this network consists of more than 26 000 protected sites covering aprox. 20% of the EU's land area. This is the largest, more complex network of environment protection in the world. It provides protection for endangered European species and habitats and, indirectly, contributes to the prosperity of the countries on whose territory it is implemented, through the ecological services provided. In Romania, at the level of 2018, the total protected areas represent about 23.65% of the total area; compared to other European countries, the area of these protected areas should be increased. But beyond the comparison with other countries, the need to increase the area of protected areas lies in the fact that, in the context of climate change on Earth, the only way in the future to safely address their effects is to protect the environment and to reduce as much as possible the anthropic “footprint”.